Tinjauan Yuridis Terhadap Perjanjian Jual Beli Secara Online Di Olx.Com Dengan Sistem Cash On Delivery (Cod) - Kurniawan, Rasyid Reza; , Nurwardhani,SH,SU (2016)
Sale and purchase in Purchase in the virtual world is certainly going to cause a problem between the seller and the buyer, because it is virtual and there are no in-person meetings between buyers and sellers but can meet directly the so-called system of Cash On Delivery (COD) provided that the seller and the buyer are in a region of the same. In sale and purchase Cash On Delivery is usually the seller advertises pictures or photos of items that will be sold through the site Olx.com, by including images or photos of items, the specification of goods, prices and phone numbers penjual. In the agreement has been set up how the process met in person in a place to negotiate the items to be purchased, the payment system. But even so, in practice there are still disputes in the forum. Some forms of the dispute based on existing cases, buyers tend to be the injured party in an online transaction cheating among other items that are not in accordance with the order and the buyer is not rigorous in checking the goods or because the seller is not honest in providing information about the goods.